2012
DOI: 10.4254/wjh.v4.i12.342
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-related hepatocellular carcinoma: An insight into molecular mechanisms and therapeutic strategies

Abstract: Hepatitis C virus (HCV) infects more than 170 million people worldwide, and thereby becomes a series global health challenge. Chronic infection with HCV is considered one of the major causes of end-stage liver disease including cirrhosis and hepatocellular carcinoma. Although the multiple functions of the HCV proteins and their impacts on the modulation of the intracellular signaling transduction processes, the drive of carcinogenesis during the infection with HCV, is thought to result from the interactions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 201 publications
0
36
0
2
Order By: Relevance
“…is increasing, leading to development of end-stage liver disease including cirrhosis and HCC [4], it is important to define mechanisms of hepatitis C virus (HCV)-induced liver carcinogenesis with involvement of the Wnt/β-catenin signaling pathway. Already at the beginning of this century more numerous mutations of β-catenin were found to develop in HCV-associated HCC than with HBV-related HCC [5].…”
mentioning
confidence: 99%
“…is increasing, leading to development of end-stage liver disease including cirrhosis and HCC [4], it is important to define mechanisms of hepatitis C virus (HCV)-induced liver carcinogenesis with involvement of the Wnt/β-catenin signaling pathway. Already at the beginning of this century more numerous mutations of β-catenin were found to develop in HCV-associated HCC than with HBV-related HCC [5].…”
mentioning
confidence: 99%
“…Different molecular pathways are speculated to be involved in the role that NS3 plays in liver fibrosis. Endogenous expression of NS3 protein inside HSCs is indicated to be fibrotic at comparable levels with core protein (Selimovic et al, 2012). Recent achievements have also suggested that the NS3 protein enhances liver fibrosis through protease activity and via direct binding to TGF-β receptors (Sakata et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of gene expression in HCV infected liver cells is supposed to play a profound role in the progression of liver fibrosis, and specific viral proteins are frequently identified to be responsible for this transformation. Modulation of gene expression by HCV NS3 protein is involved in liver disease and counts as a key mediator of disease progression toward persistent disease and clinical outcomes such as liver fibrosis, cirrhosis and HCC (Bataller et al, 2004;Selimovic et al, 2012;Wu et al, 2011;Nguyen et al, 2003). While hepatocytes are the main site of viral repli-cation, some controversial reports have claimed that HCV virus can infect hepatic stellate cells (HSCs) and modulate fibrosis signaling pathways and cell activation/transformation (Selimovic et al, 2012;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been reported in deregulated pathways of pRb in HCC. [38] TGF-β1 is the most prominent profibrogenic cytokine that can be released from any cell type during inflammation, tissue regeneration, and fibrogenesis. It is an anti-inflammatory cytokine, but TGF-β1 is a well-known tumor promoter too.…”
Section: Progression Of Hcv Infection Toward Hccmentioning
confidence: 99%